2022
DOI: 10.1111/ddg.14758
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of antithrombotic drugs in skin surgery – A survey of dermatologists in Germany

Abstract: Background:We identified substantial heterogeneity in the perioperative management of antithrombotic drugs in skin surgery in Germany in 2012 and 2017 in two cross-sectional surveys. The first national guideline on this subject was published in 2014 and updated in 2021. We sought to identify whether the management of these drugs had changed. Methods:We sent a paper-based survey to 1115 dermatologists throughout Germany asking them about their perioperative management of antithrombotic drugs in skin surgery, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The lack of robust data on the use of DOACs in this setting and the lack of specific French guidelines may explain part of this heterogeneity. Similar studies conducted in Germany 9 and among American Mohs surgeons 10 also found that practices pattern variate between surgeons, but also deviate from guidelines.…”
Section: Peri-operative Management Of Direct Xa and Iia Inhibitors Fo...mentioning
confidence: 60%
“…The lack of robust data on the use of DOACs in this setting and the lack of specific French guidelines may explain part of this heterogeneity. Similar studies conducted in Germany 9 and among American Mohs surgeons 10 also found that practices pattern variate between surgeons, but also deviate from guidelines.…”
Section: Peri-operative Management Of Direct Xa and Iia Inhibitors Fo...mentioning
confidence: 60%
“…Logically, as the size of the excision or complexity of the surgical procedure increased, the proportion of dermatologists recommending uninterrupted DOAC therapy decreased. Similarly, a more recent survey of over 250 German dermatological surgeons found the vast majority (>70%) continued rivaroxaban in the setting of small (e.g., nevus) and large (e.g., melanoma) skin excisions with practices remaining consistent between hospital and office‐based clinicians 35 . For larger excisions and sentinel lymph node biopsies (procedures only performed by the hospital‐based dermatologists surveyed), the proportions of those continuing DOAC therapy was reduced to between 15 and 30%.…”
Section: Discussionmentioning
confidence: 87%
“…Hier helfen gezielte Umfragen, wie die Untersuchung von Scherer et al. in dieser Ausgabe des JDDG [3]. Darin geht es um die Umsetzung von Empfehlungen einer inzwischen als Update vorliegenden Leitlinie zum Umgang mit Blutverdünnern bei Eingriffen an der Haut [4].…”
Section: Und Was Hat Das Mit Der Dermatologie Zu Tun?unclassified